Preoperative individual-target transcranial magnetic stimulation demonstrates an effect comparable to intraoperative direct electrical stimulation in language-eloquent glioma mapping and improves postsurgical outcome: A retrospective fiber-tracking and electromagnetic simulation study - Li, Sanzhong; Mu, Yunfeng; Rao, Yang; Sun, Chuanzhu; Li, Xiang; Liu, Huan; Yu, Xun; Yan, Xiao; Ding, Yunxia; Wang, Yangtao; Fei, Zhou (Frontiers in Oncology, 2023)
Background: Resection of glioma lesions located in brain-eloquent area needs to balance the extent of resection (EOR) and functional reservation. Currently, intraoperative direct electrical stimulation (DES) is the gold standard that guides the maximum EOR while preserving as much functionality as possible. However, intraoperative DES inevitably causes more risks of infection and epilepsy. This study aims to verify the reliability of individual-target transcranial magnetic stimulation (IT-TMS) in preoperative mapping relative to DES and evaluate its effectiveness in postsurgical outcome. Methods: A total of sixteen language-eloquent glioma patients were enrolled. Among them, nine subjects underwent preoperative nTMS mapping (n=9, nTMS group), and seven subjects belonged to non-nTMS group without prior nTMS mapping (n=7). Before surgery online IT-TMS was performed during language task in nTMS group. If this task was disturbed in consecutive three trials, this site in cortex was recorded and regarded as positive site, named nTMS hotspots (HSnTMS). Both groups were followed by awake surgery and intraoperative DES mapping. Analogous to HSnTMS, DES hotspots (HSDES) were also determined. The spatial distribution of HSnTMS and HSDES in nTMS group was recorded, registered in single brain template and compared. The center of gravity (CoG) of HSnTMS (HSnTMS-CoG)- and HSDES-CoG-based diffusion tensor imaging-fiber tracking (DTI-FT) was performed. The electromagnetic simulation was conducted and compared between nTMS and DES. Western Aphasia Battery (WAB) scale and fiber-tracking values were compared between nTMS and non-nTMS groups. Results: HSnTMS and HSDES showed a similar distribution (mean distance 6.32 ± 2.6 mm, distance range 2.2-9.3 mm, 95% CI 3.9-8.7 mm). A higher fractional anisotropy (FA) value in nTMS mapping (P=0.0373) and an analogous fiber tract length (P=0.2290) were observed. A similar distribution of electric field within brain tissues induced by nTMS and DES was noted. Compared with non-nTMS group, integration of nTMS led to a significant improvement in language performance (WAB scores, 78.4 in nTMS group vs. 69.5 in non-nTMS group, P=0.0321 < 0.05), as well as in brain structure reservation (FA value, P=0.0156; tract length, P=0.0166). Conclusion: Preoperative IT-TMS provides equally crucial data relative to DES and thus helps precise brain mapping and preserve linguistic function.